2022
DOI: 10.1021/acscatal.1c05174
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogenase-Inspired Atomically Dispersed Fe–S–C Linkages for Improved Electrochemical Reduction of Dinitrogen to Ammonia

Abstract: The electrochemical nitrogen reduction reaction (NRR) provides a sustainable alternative to the Haber−Bosch process for ammonia (NH 3 ) production. Transition metal catalysts have poor NRR performance due to the highly competitive hydrogen evolution reaction and the scaling relation between inert dinitrogen (N 2 ) and other reaction intermediates. Owing to the enhanced active sites and the anomalous quantum size effect, single-atom catalysts (SACs) have been proven to be effective in overcoming these limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 46 publications
1
42
1
Order By: Relevance
“…Sulfur was chosen as the capping functional group of clean Mo 2 C to simulate the Mo-S-Fe structure in biological nitrogen xation enzymes. 59,60 The passivated Mo 2 C surface that introduces iron (Fe) atoms and the sulfur (S) capping functional group of MXenes has been synthesized experimentally. 61 There are three functional group adsorption sites on the surface of Mo 2 C, which can be classied into the top site, hcp site and fcc site according to the coordination environment, 62 as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur was chosen as the capping functional group of clean Mo 2 C to simulate the Mo-S-Fe structure in biological nitrogen xation enzymes. 59,60 The passivated Mo 2 C surface that introduces iron (Fe) atoms and the sulfur (S) capping functional group of MXenes has been synthesized experimentally. 61 There are three functional group adsorption sites on the surface of Mo 2 C, which can be classied into the top site, hcp site and fcc site according to the coordination environment, 62 as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an essential component of chemical products, ammonia (NH 3 ) is currently one of the most important raw materials for fertilizers and has the potential to become a major form of transportable renewable energy in the future. However, the current industrial production method combining the Haber–Bosch process and steam hydrocarbon reforming has the disadvantages of high energy consumption, high pollution, need for nonrenewable energy, high temperature (about 600 °C), and pressure (about 30 MPa), which all cause obstacles to the development of future ammonia recycling economy. Therefore, the direct use of renewable electricity to convert N 2 to NH 3 [electrochemical N 2 reduction reaction (ENRR)] in small-scale electrolytic cells using H 2 O and N 2 as feedstock is a better option, which also facilitates small-scale and distributed production. However, because of the presence of competing hydrogen evolution reactions (HER), relatively weak N 2 adsorption, and slow reaction kinetics, the rate and selectivity of ENRR are inhibited. , Therefore, the ENRR process demands high-performance electrocatalysts to catalyze the complex six-electron reduction of N 2 while preventing the occurrence of competitive HER. , …”
Section: Introductionmentioning
confidence: 99%
“…Within the framework of 2D SiP, the electronegativity of Si is just a little bit lower than that of P (2.1), thus localized sites with high electron density will appear for N 2 adsorption and activation. 46 In this work, we employed density functional theory (DFT) calculations to investigate the possibility of the ENRR on 2D SiP. We found that pristine 2D SiP monolayers cannot activate inert N 2 due to surface phosphorus (P) atom covering (see Fig.…”
Section: Introductionmentioning
confidence: 99%